9-1-1 Caller-Described Heart Attack Symptoms. Issue 5 (18th October 2022) - Scott, Greg; Olola, Christopher; Miko, Matthew; Patterson, Brett; Quigg, Joleen; Davis, Chris; Lindfors, Richard; Tidwell, Jayme; Pagenkop, Kevin; Lofgren, John; Fox, Jaci; Clawson, Jeff
Abstract: Introduction: Heart attacks (HAs) present clinically with varying symptoms, which are not always described by patients as chest pain (CP) or chest discomfort (CD). Emergency Medical Dispatchers (EMDs) select the CP/CD dispatch protocol for non-chest pain HA symptoms or classic HA complaint of CP/CD. Nevertheless, it is still unknown how often callers report HA symptoms other than CP/CD. Objectives: The objective of this study was to characterize the caller's descriptions of the primary HA symptoms, descriptions of the other HA symptoms, and the use of a case entry (CE) question clarifier. Methods: A retrospective descriptive study analyzed randomly selected EMD audios (where CD/CD protocol was used) from five accredited emergency communication centers in the United States. Several Quality Performance Review (QPR) experts reviewed the audios and recorded callers' initial problem descriptions, the use of and responses to the CE question clarifier, including the EMD-assigned final determinant code. Results: A total of 1, 261 audios were reviewed. The clarifier was used only 8.5% of the time. The CP/CD symptoms were mentioned alone or with other problems 87.0% of the time. Overall, CP symptom was mentioned alone 70.8%, HA alone 4.0%, and CD symptom alone 1.4% of the time. Conclusion: 9-1-1 callers report potential HA cases using a variety of terms and descriptions—most commonly CP. Other less-common symptoms associated with a HA may be mentioned. Therefore, EMDs must be well-trained to be prepared to probe the caller with a clarifying query to elicit more specific information when "having a heart attack" is the only complaint initially mentioned.